Unpredictable Cryptographic Pseudo-Random Number Generator based on Non-linear Dynamic Chaotic System - Čitavičius, A.; Jonavičius, A.; Japertas, S. (Elektronika ir Elektrotechnika, 2007)
Most of pseudo-random number generators are unsuitable for cryptographic applications despite their statistical and correlation characteristics due to its backward and forward predictability. The prediction can be performed by noticing (or recovering) some output sequences of generators. To solve this problem, we recommend using a non-linear dynamic chaotic system and an auxiliary generator with complex structure, based on pseudo-random number generators, which produce secret parameter β necessary for non-linear dynamic chaotic system. Thus we get an unpredictable cryptographic pseudo-random number generator based on non-linear dynamic chaotic system with forward and backward unpredictable properties. The theoretical background and possible structure of cryptographic secure pseudo-random number generator are presented. Ill. 2, bibl. 7 (in English; summaries in English, Russian and Lithuanian).